Etiology of Syncope and Unexplained Falls in Elderly Adults with Dementia: Syncope and Dementia (SYD) Study. Issue 8 (28th June 2016) - Ungar, Andrea; Mussi, Chiara; Ceccofiglio, Alice; Bellelli, Giuseppe; Nicosia, Franco; Bo, Mario; Riccio, Daniela; Martone, Anna Maria; Guadagno, Livia; Noro, Gabriele; Ghidoni, Giulia; Rafanelli, Martina; et al.
Abstract : Objectives: To investigate the etiology of transient loss of consciousness (T‐LOC) suspected to be syncope and unexplained falls in elderly adults with dementia. Design: Prospective, observational, multicenter study. Setting: Acute care wards, syncope units or centers for the diagnosis of dementia. Participants: Individuals aged 65 and older with a diagnosis of dementia and one or more episodes of T‐LOC of a suspected syncopal nature or unexplained falls during the previous 3 months were enrolled. Measurements: The causes of T‐LOC suspected to be syncope and unexplained falls were evaluated using a simplified protocol based on European Society of Cardiology guidelines. Results: Of 357 individuals enrolled, 181 (50.7%) had been referred for T‐LOC suspected to be syncope, 166 (46.5%) for unexplained falls, and 10 (2.8%) for both. An initially suspected diagnosis of syncope was confirmed in 158 (87.3%), and syncope was identified as the cause of the event in 75 (45.2%) of those referred for unexplained falls. Orthostatic hypotension was the cause of the event in 117 of 242 (48.3%) participants with a final diagnosis of syncope. Conclusion: The simplified syncope diagnostic protocol can be used in elderly people with dementia referred for suspected syncope or unexplained falls. Unexplained falls may mask a diagnosis of syncope or pseudosyncope in almost 50% of cases. Given the high prevalence of orthostatic syncope in participants (~50%), a systematic reappraisal of drugs potentially responsible for orthostatic hypotension is warranted.